THE ESTABLISHMENT THE UNIQUE POSITION OF INTELLECTUALS IN MA VAN KHANG’S NOVELS - Ho Thi Phuong Mai (Tạp chí Khoa học, 2023)
Ma Van Khang is a prominent novelist who has made significant contributions by delving into the subject of intellectuals. The author often contemplates the role of intellectuals in the society. There have been numerous research works on this central theme in Ma Van Khang's novels, and they have provided valuable assessments. However, interpreting Ma Van Khang's artistic choices and the depth of his perspective on the issues he addresses continue to provoke discussions. By situating Ma Van Khang's novels within the broader context of the fluctuating currents of modern Vietnamese fiction that focus on intellectuals and by examining the author's consciousness of the dynamic relationship between literature and life, this article contributes to explaining why the issues raised in the writer's works and the way he presents them have garnered positive responses from readers.